Tipping the Scales With Zebrafish to Understand Adaptive Tumor Immunity - Miao, Kelly Z.; Kim, Grace Y.; Meara, Grace K.; Qin, Xiaodan; Feng, Hui (Frontiers in Cell and Developmental Biology, 2021)
The future of improved immunotherapy against cancer depends on an in-depth understanding of the dynamic interactions between the immune system and tumors. Over the past two decades, the zebrafish has served as a valuable model system to provide fresh insights into both the development of the immune system and the etiologies of many different cancers. This well-established foundation of knowledge combined with the imaging and genetic capacities of the zebrafish provides a new frontier in cancer immunology research. In this review, we provide an overview of the development of the zebrafish immune system along with a side-by-side comparison of its human counterpart. We then introduce components of the adaptive immune system with a focus on their roles in the tumor microenvironment of teleosts. In addition, we summarize zebrafish models developed for the study of cancer and adaptive immunity along with other available tools and technology afforded by this experimental system. Finally, we discuss some recent research conducted using the zebrafish to investigate adaptive immune cell-tumor interactions. Without a doubt, the zebrafish will arise as one of the driving forces to help expand the knowledge of tumor immunity and facilitate the development of improved anti-cancer immunotherapy in the foreseeable future.